Increasing MSME Competitiveness through Green Marketing Implementation: The Case of Pematang Serai Village, Langkat - Sanny, Annisa; Daulay, Muhamad Toyib; Ritonga, Husni Muharram; Putri, Indry Febrianti (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the role of Green Marketing implementation in increasing the competitiveness of Micro, Small and Medium Enterprises (MSMEs) in Pematang Serai Village, Langkat. Case studies are conducted using a quantitative approach, data type. What is used in this study is primary data taken through direct research, also with secondary data as support. The results showed that the implementation of Green Marketing significantly contributed to increasing the competitiveness of MSMEs in Pematang Serai Village. Through environmentally friendly and sustainable marketing practices, MSMEs are able to create competitive advantages, improve brand image, and attract the attention of consumers who care about the environment. The implications of this research provide guidance for stakeholders to strengthen Green Marketing strategies in supporting the growth and sustainability of MSMEs at the village level.